1989
DOI: 10.1007/bf00004721
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic control of prolactin release in the rainbow trout,Salmo gairdneri: in vitro studies

Abstract: Hypothalamic control of prolactin (PRL) release in immature rainbow troutSalmo gairdneri was investigated using anin vitro perifusion system of the rostral pars distalis. Hypothalamic extract of trout induced a dose-dependent stimulation of PRL release. A similar effect was observed when infusing the medium from a 24h static incubation of the hypothalamus. Extracts from different control tissues (muscle, liver, gut) did not changein vitro release, thus confirming the specificity of this stimulatory effect. Hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…This is in agree¬ ment with a study on prolactin and GH release from the pituitary of rainbow trout in culture (Yada et al 1991). These authors concluded a dominant stimula¬ tory control of rainbow trout prolactin cells by the hypothalamus, as suggested by Gönnet et al (1989), and a dominant inhibitory control for GH cells. Such particular dominant controls of prolactin and GH secretion in rainbow trout, the converse of those described in mammals, are reflected in the present time-course study of the effects of SRIF on prolactin and GH release from trout pituitary cells in culture.…”
Section: Discussionsupporting
confidence: 87%
“…This is in agree¬ ment with a study on prolactin and GH release from the pituitary of rainbow trout in culture (Yada et al 1991). These authors concluded a dominant stimula¬ tory control of rainbow trout prolactin cells by the hypothalamus, as suggested by Gönnet et al (1989), and a dominant inhibitory control for GH cells. Such particular dominant controls of prolactin and GH secretion in rainbow trout, the converse of those described in mammals, are reflected in the present time-course study of the effects of SRIF on prolactin and GH release from trout pituitary cells in culture.…”
Section: Discussionsupporting
confidence: 87%
“…The localization to a particular site could help the hypothalamus to innervate prolactin cells and regulate their functions. While dopamine receptors in prolactin cells inhibit prolactin release in both mammals and teleosts [7,18], teleostean hypothalamic prolactin releasing factor (PRF) plays a more prominent role than that of mammals [19]. Dopamine not only acts on D 2 -receptors in prolactin cells, but also stimulates GH secretion through D 1 -like-receptors [20] and modulates GTH secretion in teleosts [21,22].…”
Section: Discussionmentioning
confidence: 99%